Creation and validation of a novel body condition scoring method for the magellanic penguin (Spheniscus magellanicus) in the zoo setting. Issue 6 (25th August 2015) - Clements, Julie; Sanchez, Jessica N.
Abstract : This research aims to validate a novel, visual body scoring system created for the Magellanic penguin ( Spheniscus magellanicus ) suitable for the zoo practitioner. Magellanics go through marked seasonal fluctuations in body mass gains and losses. A standardized multi‐variable visual body condition guide may provide a more sensitive and objective assessment tool compared to the previously used single variable method. Accurate body condition scores paired with seasonal weight variation measurements give veterinary and keeper staff a clearer understanding of an individual's nutritional status. San Francisco Zoo staff previously used a nine‐point body condition scale based on the classic bird standard of a single point of keel palpation with the bird restrained in hand, with no standard measure of reference assigned to each scoring category. We created a novel, visual body condition scoring system that does not require restraint to assesses subcutaneous fat and muscle at seven body landmarks using illustrations and descriptive terms. The scores range from one, the least robust or under‐conditioned, to five, the most robust, or over‐conditioned. The ratio of body weight to wing length was used as a "gold standard" index of body condition and compared to both the novel multi‐variable and previously used single‐variable body condition scores. The novel multi‐variable scale showed improved agreement with weight:wing ratio compared to the single‐variable scale, demonstrating greater accuracy, and reliability when a trained assessor uses the multi‐variable body condition scoring system. Zoo staff may use this tool to manage both the colony and the individual to assist in seasonally appropriate Magellanic penguin nutrition assessment. Zoo Biol. 34:538–546, 2015. © 2015 Wiley Periodicals, Inc.